Integrity Challenges of Audio-Visual Journalism in the Era of Artificial Intelligence - Abdul Syukur; Faisal Utama; Edison Bonar Tua Hutapea (PT. Student Rihlah Indonesia, 2026)
Maintaining integrity and professional morality amid the secondary disruption of the broadcasting media industry due to Artificial Intelligence (AI) integration has become crucial and vital. AI carries the risk of bias and hallucination, while regulations are not yet fully capable of anticipating this